(-x)-4x=3-6x

Simple and best practice solution for (-x)-4x=3-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-x)-4x=3-6x equation:


Simplifying
(-1x) + -4x = 3 + -6x

Combine like terms: (-1x) + -4x = -5x
-5x = 3 + -6x

Solving
-5x = 3 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-5x + 6x = 3 + -6x + 6x

Combine like terms: -5x + 6x = 1x
1x = 3 + -6x + 6x

Combine like terms: -6x + 6x = 0
1x = 3 + 0
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| 10x-3=8r+4 | | (x+2)-2(4-3x)=5(x+5)-1 | | 24x^2-14x=0 | | 16x^2+40x-96=0 | | 8.00(4.00+x)=72 | | 3(4x-3)+1=(3x-1)-2(x-2) | | (-x)-46=3-6x | | 12a-13=3 | | 2x^3-11x^2+5x=0 | | .30x+.05(10-x)=.10(20) | | 3(2x-2)=-4(x+4) | | 2x^3+5x^2-14x-8=0 | | 2x^2-120=0 | | -3h+21-3=-2-3h+12+13h | | (4u+3)(8-u)=0 | | 7x-2x(x-3)=5x+2 | | 3m-5n=8r | | 5h+7-2h-3=-2 | | x+11=3x+3 | | 3.04=x+1.52x | | 3(x+9)=12 | | x=3p+n | | 16x^2+64x+60=0 | | 5xa=120 | | 14x-29=-13 | | 16x^2+64+60=0 | | 0.2x-8=-2-z | | 5x-11=3x+4 | | 2x^2+21x=-54 | | 8j+4-3h=1+4h-2 | | 3x+2(x-2)=4x-23+2x | | 14c+7-8c=37 |

Equations solver categories